Primus Nurudong's Ghana Zoom transcript, September 13, 2021 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2021)
To have access to the research data file, please contact: Nurudong Primus nurudong5282@gmail.com
Keywords: Travel; Schools; Food security; Vaccination; Lockdown; Burkina Faso; Ghana; Border; Mobility; COVID-19 Pandemic